When Civil Society Leads: Advocacy Coalitions and the Making of Disability Policy in Jakarta - Ade Siti Barokah; Evi Satispi; Sa’diyah El Adawiyah; Bambang Soetono (Universitas Muhammadiyah Jakarta, 2025)
This study examines the formulation process of Jakarta Provincial Regulation No. 4 of 2022 on the Fulfilment of the Rights of Persons with Disabilities, focusing on the role of Disabled People’s Organizations (DPOs) in shaping policy outcomes. Using a qualitative approach, data were collected through in-depth interviews and observations involving key actors across policy levels. The study applies the Advocacy Coalition Framework (ACF) and Collaborative Governance to analyze actor interactions, belief systems, and institutional dynamics. The findings reveal that policy formulation was significantly influenced by self-initiated collaboration among DPOs, challenging dominant assumptions that collaborative governance is state-driven. The study also identifies asymmetrical power relations and institutional constraints that shape participation and influence. This research contributes to theoretical development by contextualizing ACF and collaborative governance in the Global South and offers a model for inclusive policy formulation involving marginalized groups.